The Use of BDDCS in Classifying the Permeability of Marketed Drugs() - Benet, Leslie Z. (2008)
We recommend that regulatory agencies add the extent of drug metabolism (i.e., ≥90% metabolized) as an alternate method in defining Class 1 marketed drugs suitable for a waiver of in vivo studies of bioequivalence. That is, ≥90% metabolized is an additional methodology that may be substituted for ≥90% absorbed. We propose that the following criteria be used to define ≥ 90% metabolized for marketed drugs: Following a single oral dose to humans, administered at the highest dose strength, mass balance of the Phase 1 oxidative and Phase 2 conjugative drug metabolites in the urine and feces, measured either as unlabeled, radioactive labeled or nonradioactive labeled substances, account for ≥ 90% of the drug dosed. This is the strictest definition for a waiver based on metabolism. For an orally administered drug to be ≥ 90% metabolized by Phase 1 oxidative and Phase 2 conjugative processes, it is obvious that the drug must be absorbed. This proposal, which strictly conforms to the present ≥90% criteria, is a suggested modification to facilitate a number of marketed drugs being appropriately assigned to Class 1.